ARTIFICIAL INTELLIGENCE AND SECONDARY EDUCATION IN INDIA - Pathak, Rekha A; Waghmare, Suresh S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence (AI) has the potential to revolutionize various sectors, and secondary education in India is no exception. This paper explores the integration of AI in India’s secondary education system, highlighting its potential benefits, challenges, and the roadmap for effective implementation. It aims to provide a comprehensive understanding of how AI can enhance the quality of education, personalize learning experiences, and bridge the educational divide in the country.